Radical Addition/Cyclization Cascade: An Efficient Approach to Nitro-Containing Quinoline-2,4(1H,3H)-diones - Yang, Tao; Zhou, Jia-Li; Li, Junpeng; Shen, Yuehai; Gao, Chuanzhu; Li, Ya-Min (Synthesis, 2018)
A radical addition/cyclization cascade of o-cyanoarylacrylamides with magnesium nitrate hexahydrate is developed. This reaction exhibits good functional group tolerance and wide substrate scope, provides a highly efficient and practical access to nitro-containing quinoline-2,4(1H,3H)-diones.
Keywords: quinoline-2,4(1H,3H)-dione; nitro; radical; cascade; nitrile